The Effect of Parental Presence on The Anxiety Level of Nurses During Intravenous Interventions in Children - İlknur Coşgun; Selmin Köse (National Scientific Medical Center, 2024)
Aim: The present study employed an analytical, cross-sectional, and pretest-posttest design to assess the impact of parental presence on the anxiety levels of nurses during intravenous interventions in pediatric patients. Materials and Methods: The research was conducted in a public hospital in Istanbul between 01 September and 30 December 2021. The population of the research consisted of nurses working in the pediatric clinic of the hospital (N = 70), and the sample consisted of 50 nurses who met the research criteria and agreed to participate in the research. Data were obtained through an information form and a state-trait anxiety inventory. Participants were first asked to fill out the information form and the trait anxiety inventory. The research was carried out in two phases with the same sample group. In the first phase, nurses were asked to fill out the state anxiety inventory immediately after intravenous interventions were administered to children while their parents were with their children. In the second phase, after a period of 15 days, a state anxiety inventory was applied to the nurses with the same sample group immediately after the intravenous interventions, without the participation of the family. The SPSS 26 package statistical program was used to evaluate the data. Result and Conclusion: It was determined that the mean trait anxiety scores of the participants were at a medium level and that the mean state anxiety scores of the nurses were statistically significantly higher (p<0.001) in the interventions in which the parents were included in the process compared to the interventions in which the parents were not included in the process. Continuous in-service training can be recommended for pediatric nurses to adopt family-centered care.